The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1242/dmm.032698
|View full text |Cite
|
Sign up to set email alerts
|

Pgc-1α repression and high-fat diet induce age-related macular degeneration-like phenotypes in mice

Abstract: Age-related macular degeneration (AMD) is the major cause of blindness in the elderly in developed countries and its prevalence is increasing with the aging population. AMD initially affects the retinal pigment epithelium (RPE) and gradually leads to secondary photoreceptor degeneration. Recent studies have associated mitochondrial damage with AMD, and we have observed mitochondrial and autophagic dysfunction and repressed peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α; also known as Pparg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 52 publications
(68 reference statements)
2
38
0
Order By: Relevance
“…These results therefore suggest that PGC-1α may be protective in microvascular diseases, including retinopathies. In line with these results, PGC-1α heterozygous mice exposed to a high fat diet developed age-related macular degeneration-like abnormalities in the retinal pigmented epithelium and local inflammatory responses [83]. In the context of kidney diseases, endothelial dysfunction associated with hypertension, obesity and/or diabetes is a key mechanism in CKD progression and CKD-related cardiovascular complications [84][85][86][87].…”
Section: Endotheliumsupporting
confidence: 53%
“…These results therefore suggest that PGC-1α may be protective in microvascular diseases, including retinopathies. In line with these results, PGC-1α heterozygous mice exposed to a high fat diet developed age-related macular degeneration-like abnormalities in the retinal pigmented epithelium and local inflammatory responses [83]. In the context of kidney diseases, endothelial dysfunction associated with hypertension, obesity and/or diabetes is a key mechanism in CKD progression and CKD-related cardiovascular complications [84][85][86][87].…”
Section: Endotheliumsupporting
confidence: 53%
“…Mechanistic insights into mitochondrial dysfunction in AMD have highlighted a protective role for proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) in RPE during AMD [94,108]. Repression of PGC-1α in mice and exposure to a high-fat diet resulted in AMD-like abnormalities in the RPE [109]. Work in our laboratory identified PGC-1α as a master regulator of mitochondrial biogenesis and function in RPE, increasing in expression with RPE maturation [110].…”
Section: Metabolic Dysfunction and Autophagy In Amdmentioning
confidence: 97%
“…However, it is justified to state that PGC-1α impairment in the retina may result in AMD or AMD-like state. Moreover, it can be speculated that autophagy and mitochondrial quality control can be involved, and this speculation has been recently supported by experiments of Zhang et al [114]. These authors showed that mice with the deletion of one copy of the PGC-1α gene and fed with a fat-rich diet showed AMD-like phenotype in RPE, including diminished mitochondrial activity and autophagic flux.…”
Section: Discussionmentioning
confidence: 89%